Financial Inclusion and Poverty Alleviation in Akwa Ibom State, Nigeria: The Case Study of Small and Medium Enterprises - Ndem, Bassey Enya; Walter, Mboto Hellen; Henry, James Tumba; Peter, Lebo Monica; Ita, Asuquo Joseph (International Journal of Economics and Financial Issues, 2022)
The purpose of the study is to investigate the impact of financial inclusion on poverty alleviation among SMEs in Akwa Ibom State, Nigeria. Data collection techniques employed was self-administered questionnaire. The questionnaires were administered to a total of 295 respondents who are operators of SMEs in Akwa Ibom State, Nigeria by using purposive sampling technique. In analyzing the relationship among the variables, Spearman rank correlation was adopted. The findings of the study revealed that financial inclusions in terms of bank loans to SMEs operators do not have statistical significant correlation with poverty alleviation in Akwa Ibom State while financial inclusion in terms of access to ATM and internet banking do have statistical significance correlations with poverty alleviation among SMEs operators in Akwa Ibom State. Hence, the policy implication of the study is that banks should reduce their interest rate in order to induce SMEs operators to access bank loans for their businesses.